Which variables matter for process design and scale-up? a study of sugar cane straw pretreatment using low-cost and easily synthesizable ionic liquids - Ferrari, Felipe Augusto; Pereira, Jorge Fernando Brandaõ [UNESP]; Witkamp, Geert-Jan; Forte, Marcus Bruno Soares (American Chemical Society (ACS), 2019)
Ionic liquids (ILs) have great potential as solvents and catalysts for pretreatment of lignocellulosic biomass. However, process scale-up necessitates that IL-based pretreatment methods be optimized in terms of cost and sustainability. In this study, low-cost and easily synthesizable ethanolammonium-based ILs were prepared and used in the pretreatment of sugar cane straw (SW). The effects of ILs, IL mixtures, pretreatment temperature, water content, solids loading, ultrasonication, and agitation speed on residual solids enzymatic digestibility and delignification were systematically assessed, and the process was scaled up from a 50 mL static flask to a 1 L impelled reactor. IL mixtures improved enzymatic digestibility at higher solids loading and water addition in the reaction medium under mild temperature conditions (90 °C). Enzymatic hydrolysis of residual solids after bench-scale pretreatment of SW for 3 h at 15% (w/w) solids loading and 20% (w/w) water content in the liquid phase resulted in 98% cellulose digestibility under nonoptimized conditions. This study provides a practical review of IL-based pretreatment methods, discusses the selection of variables for process design and scale-up, and presents empirical results.
Keywords: Effect; Ionic liquid; Lignocellulose; Pretreatment; Process design; Variables